2017
DOI: 10.5194/acp-2017-987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantification of sulfur deposition changes under sulfate geoengineering conditions

Abstract: Abstract.Sustained injection of sulfur dioxide (SO 2 ) in the tropical lower stratosphere has been proposed as a climate engineering technique with the purpose of temporarily mitigating the surface warming predicted for the coming decades. Among several possible environmental side effects, the increase of sulfur deposition at the ground surface still needs to be thoroughly investigated. In this study we present results from a composition-climate coupled model (ULAQ-CCM) and a chemistry-transport 5 model (GEOS-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This is consistent with the findings of Visioni et al (2017b): the aerosol-driven surface cooling in G4 (contrary to G4K) favors a decreased wave activity and a consequent decrease in poleward mass fluxes from the tropical reservoir, for both gas and aerosol species. On the other Niemeier and Schmidt (2017); Visioni et al (2017c)). On light of this, smaller stratospheric heating rate anomalies are calculated in G4 with respect to G4K (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with the findings of Visioni et al (2017b): the aerosol-driven surface cooling in G4 (contrary to G4K) favors a decreased wave activity and a consequent decrease in poleward mass fluxes from the tropical reservoir, for both gas and aerosol species. On the other Niemeier and Schmidt (2017); Visioni et al (2017c)). On light of this, smaller stratospheric heating rate anomalies are calculated in G4 with respect to G4K (Fig.…”
mentioning
confidence: 99%
“…In particular, the lower stratosphere (LS) warming, caused by increasing heating rates in the optically thick sulfate cloud, tends to decrease the tropospheric lapse rate. A subsequent decrease in the available turbulent kinetic energy (TKE) would follow and translate 5 in slowing down updraft of water vapor to the UT, thus reducing the probability for sufficiently high supersaturation values capable to produce ice crystals formation via homogeneous freezing. Their study found a resulting large net RF reduction in magnitude with respect to clear sky conditions, where only the direct aerosol forcing is considered (-0.93 The aforementioned study, however, lacked an important part of the possible dynamical feedback of SG, that is changes in sea surface temperatures (SSTs) that would result from the decreased incoming solar radiation.…”
mentioning
confidence: 99%
See 2 more Smart Citations